Tilsa in the adventurous path of Noé Delirante by Arturo Corcuera - Rocha Puente, Ana María (2020)
This article addresses an instance of the creative link between two important artists in contemporary Peruvian culture: painter Tilsa Tsuchiya and poet Arturo Corcuera, who forged a productive friendship which translated into artistic collaboration. Through the formal and semantic analysis of a poem from the book Noé delirante by Corcuera and its respective illustration made by Tsuchiya, the article seeks to find the relationships of signification that connect both works.